If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 2) + -2(3x + -4) + -11x = 0 Reorder the terms: 3(2 + 2x) + -2(3x + -4) + -11x = 0 (2 * 3 + 2x * 3) + -2(3x + -4) + -11x = 0 (6 + 6x) + -2(3x + -4) + -11x = 0 Reorder the terms: 6 + 6x + -2(-4 + 3x) + -11x = 0 6 + 6x + (-4 * -2 + 3x * -2) + -11x = 0 6 + 6x + (8 + -6x) + -11x = 0 Reorder the terms: 6 + 8 + 6x + -6x + -11x = 0 Combine like terms: 6 + 8 = 14 14 + 6x + -6x + -11x = 0 Combine like terms: 6x + -6x = 0 14 + 0 + -11x = 0 14 + -11x = 0 Solving 14 + -11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -11x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -11x = 0 + -14 -11x = 0 + -14 Combine like terms: 0 + -14 = -14 -11x = -14 Divide each side by '-11'. x = 1.272727273 Simplifying x = 1.272727273
| 3/2v+2=10 | | -2x-6=-6-2 | | -2(y+3)-3(2y-6)-14y= | | c=3b+4a-p | | 3(4x+6)-36= | | -1/3+4/5u=-3/2 | | z^2=5 | | 13(t-1)=8t-(8-5t) | | 1/3(5y-2)+1/6(8y+6) | | z^2-5=0 | | 4/7x+5/9 | | 8x+3/4=9x-9/4 | | (x+19)+(3x-22)+x=572 | | n+4=3n+22 | | (x+19)+(22-3x)+x=572 | | 0.80x+0.50(100)=0.40(65) | | 8^5+16w^3/4w | | 5n-17=11+3n | | (x+19)+(22-3x)=x | | 2x+3(2x-7)=-14 | | 2x+3(2x)-7=-14 | | (x+19)+(22-4x)+x=572 | | .8(.1x+.5)=-.8 | | -5x+6=-2(4y+3) | | p=(2*23)+(2*45) | | -1/2x-5y=6 | | -2[(-3-2)-2(-2+m)]=-3m-16-2 | | -2x/3-2=-7 | | 68x=95.2 | | (x+400000)+x=600000000 | | 9(x-5)-2=-47 | | (9/4)x+1 |